Model of Arabic Language Learning Management in Child-Friendly Schools for the Development of Character Education in the Independent Curriculum - Nasarudin Nasarudin; Nurjannah Nurjannah; Muhirdan Muhirdan; Ahmad Helwani Syafii; Husnan Husnan; Henny Marlina (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
A collegial management model was used in the implementation of the Child-Friendly School (CFS) policy at MIN 1 Mataram in developing character education in the Independent Curriculum, which has implications for Arabic learning management. This article presented the discover and analysis of the Arabic language learning management model in instilling character education for the Independent Curriculum at the Child-Friendly School. A qualitative approach was used with a case study method, utilizing Miles and Huberman's data analysis techniques. The analysis process began with data condensation, which involves reducing information obtained from interviews, observations, and document analyses to filter relevant data. Next, data presentation was carried out by providing information in the form of descriptive narratives that illustrate the management of Arabic language learning. Finally, conclusions were drawn by identifying patterns, themes, and relationships among the data to understand the management model in character education.The finding showed that the CFS Arabic learning management model in instilling character education for the Independent Curriculum at MIN 1 Mataram used the Deming Cycle Model PDCA (Plan-Do-Check-Act), integrating the Plan, Do, and Check stages with the CFS principles. In the plan stage, teachers design character-based ATPs (syllabus) and Teaching Modules (Lesson Plan), collaborate in planning, and adapt teaching materials to student needs. The Do stage involves implementing the module with a differentiated approach and learning methods that emphasize character. In Check, evaluation involves principals, teachers, and students, ensuring learning effectiveness and positive perceptions of Arabic. This process supports continuous improvement in child-friendly teaching.